Knowledge, practice and professional identity: unthreading the challenges of contemporary police tutoring arrangements in England and Wales - Cockcroft, Tom (Policing and society, 2025)
Police tutoring, to date, has received little attention from researchers and what research currently exists points to a system that is largely failing. The current research was undertaken in response to a range of concerns including those relating to the impact on tutoring of a new underpinning educational framework (Policing Education Qualifications Framework) and a substantial increase in police recruitment (Police Uplift Programme). The research is unique in that it explores these challenges through the context of different delivery models. The data upon which this paper draws consists of survey data returned from each of the 43 Home Office funded forces in England and Wales, 22 semi-structured interviews and four focus groups. Descriptive and thematic analysis of this data allowed the authors to identify four inter-related themes which will be reported on in this paper – ‘Different Models of Tutoring Delivery’, ‘Structure of Tutoring Arrangements’, ‘Status of Tutoring’ and ‘Classroom, Practice-based and Reflective Learning’. These point to the nuanced relationship between structural arrangements for tutoring delivery, the value which police organisations attribute to tutoring and the impact of these on the ways in which ‘learning’ is positioned within these arrangements. In doing so, this draws attention to the apparently intractable tension between ‘legalistic’ and ‘autonomous’ perspectives on policing (Fekjaer and Petersson [2020]. Producing legalists or Dirty Harrys? Police education and field training. In: T. Bjorgo and M.-L. Damen, eds. The making of a police officer: comparative perspectives on police education and recruitment. Abingdon: Routledge, 208). The paper concludes that police tutoring arrangements exist without a defined set of underlying pedagogic principles, are often primarily focused on enabling organisational capacity and conflate organisational socialisation with the translation of knowledge into practice.